The influence of standards and clinical guidelines on prosthetic and orthotic service quality: a scoping review. Issue 20 (25th September 2018) - Sadeghi-Demneh, Ebrahim; Forghany, Saeed; Onmanee, Pornsuree; Trinler, Ursula; Dillon, Michael P.; Baker, Richard
Abstract: Objectives: Standards and guidelines are an integral part of prosthetic and orthotic service delivery in the developed world underpinned by an assumption that they lead to improved services. Implementing them has a cost, however, and that cost needs to be justified, particularly in resource-limited environments. This scoping review thus asks the question, "What is the evidence of the impact of standards and guidelines on service delivery outcomes in prosthetics and orthotics?" Materials and methods: A structured search of three electronic databases (Medline, Scopus and Web of Science) followed by manual searching of title, abstract and full text, yielded 29 articles. Results: Four categories of papers were identified: Descriptions and Commentaries (17 papers), Guideline Development (7), Guideline Testing (2) and Standards implementation (3). No articles were explicitly designed to assess the impact of standards and guidelines on service delivery outcomes in prosthetics and orthotics. Discussion and conclusion: Studies tended to be commentaries on or descriptions of guideline development, testing or implementation of standards. The literature is not sufficiently well developed to warrant the cost and effort of a systematic review. Future primary research should seek to demonstrate whether and how guidelines and standards improve the outcomes for people that require prostheses, orthoses and other assistive devices. Implications for Rehabilitation: International Standards and Clinical Guidelines are now an integral part of clinical service provision in prosthetics and orthotics in the developed world. Complying with standards and guidelines has a cost and, particularly in resource-limited environments, it should be possible to justify this in terms of the resulting benefits. This scoping review concludes that there have been no previous studies designed to directly quantify the effects of implementing standards and guidelines on service delivery.